The Strategy of Forming Religious Characters on the Deaf Children: Study at Special Schools in Rejang Lebong - Ahmad Suradi; Mawardi Mawardi (Institut Agama Islam Negeri Imam Bonjol Padang, 2020)
The study aims to determine the strategy used in forming religious characters on the deaf children in Elemantary Special School. A qualitative method was used where the data taken from observation, interview and document analysis. The result showed that the learning strategy of Islamic religious education in the development of morals for children with special needs in special schools is by implementing expository strategy, adding hours of study using the habituation method. The finding also showed that the supporting factors in the learning process to form moral guidance are the involvement of school’s principal who is very concern on the development of students’ morals; the teachers who have great patience in dealing with children with special needs. Then, it was also found that there were some inhibiting factors that faced by the school. They were on the absence of a special curriculum for children with special needs, Islamic education teachers who are not teachers who are graduates of special service schools, as well as the lack of supporting facilities as learning media, doing the learning process run monotonously.